2014
DOI: 10.1016/j.jtcvs.2013.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Low serum sodium level during cardiopulmonary bypass predicts increased risk of postoperative stroke after coronary artery bypass graft surgery

Abstract: An average serum sodium level of less than 130 mEq/L during cardiopulmonary bypass is independently associated with an increased risk of postoperative stroke in patients who undergo primary coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…(Mangano et al, 1998) Mannitol has been shown to enhance blood flow to the kidneys, which may benefit renal function in cases of acute kidney damage that occur after heart surgery (Bragadottir et al, 2012;Sirivella et al, 2000) However, a number of studies show that mannitol causes enhanced endothelial cell death and that this might be detrimental in cases of acute renal damage (Malek et al, 1998;Moreira et al, 2017;Zhang et al, 1999 (Manninen et al, 1987) Our data supported these conclusions by demonstrating that, after CABG, the Mannitol group's sodium concentration was noticeably lower. Mannitol inhibits the reabsorption of sodium in the tubules of the kidney in addition to the plasma sodium dilution action, which may lead to the onset of low sodium levels during CBP (Wong et al, 1979) Research indicates that hyponatremia carries a risk of cerebral edema and is, hence, potentially harmful (Adrogué and Madias, 2000;Crestanello et al, 2013;Munoz III et al, 2014) The result following heart surgery may be improved by reducing the risk of hyponatremia (Crestanello et al, 2013); in particular, avoiding hyponatremia during CPB is crucial. Using a prime solution devoid of mannitol might help accomplish this objective.…”
Section: Resultsmentioning
confidence: 99%
“…(Mangano et al, 1998) Mannitol has been shown to enhance blood flow to the kidneys, which may benefit renal function in cases of acute kidney damage that occur after heart surgery (Bragadottir et al, 2012;Sirivella et al, 2000) However, a number of studies show that mannitol causes enhanced endothelial cell death and that this might be detrimental in cases of acute renal damage (Malek et al, 1998;Moreira et al, 2017;Zhang et al, 1999 (Manninen et al, 1987) Our data supported these conclusions by demonstrating that, after CABG, the Mannitol group's sodium concentration was noticeably lower. Mannitol inhibits the reabsorption of sodium in the tubules of the kidney in addition to the plasma sodium dilution action, which may lead to the onset of low sodium levels during CBP (Wong et al, 1979) Research indicates that hyponatremia carries a risk of cerebral edema and is, hence, potentially harmful (Adrogué and Madias, 2000;Crestanello et al, 2013;Munoz III et al, 2014) The result following heart surgery may be improved by reducing the risk of hyponatremia (Crestanello et al, 2013); in particular, avoiding hyponatremia during CPB is crucial. Using a prime solution devoid of mannitol might help accomplish this objective.…”
Section: Resultsmentioning
confidence: 99%
“…Because an average serum sodium level<130 mEq/mL after crossclamp is independently associated with an increased risk of postoperative stroke in patients undergoing coronary artery bypass grafting. 13 differences in occurrence of serum sodium levels 130 mEq/L after aortic crossclamp and seizures between the 2 groups were reported in terms of odds ratios (OR) and 95% confidence interval (CI). Logistic regression analyses were used to identify risk factors for serum sodium levels <130 mEq/L after aortic crossclamp.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the plasma sodium dilution effect, mannitol causes inhibition of sodium reabsorption in renal tubules, which may contribute to the development of hyponatremia during CBP. It has been shown that hyponatremia is a potentially dangerous condition associated with the risk of brain edema . Another serious condition, central pontine myelinolysis, may occur when hyponatremia is treated rapidly .…”
Section: Discussionmentioning
confidence: 99%